DECISION MAKING IN DECENTRALIZED FOREST MANAGEMENT: Cases of Dimako Council and Nkongo Community Forests, Cameroon - Nkafu, Stella Njikem (My University, 2014)
Cameroon has since launched a restructuring of its forest resource management in 1994, predicted on the assumption that positive socio economic change, popular participation and, poverty alleviation will be achieved from the transfer of decision making functions and management responsibilities and benefits to local communities. The local communities saw the advent of the forest legislation which outlined the transfer of the forest management responsibilities to them as a response to their age old demand of access to financial benefit from forest and local development. However, detailed examination proves that decentralized forms of local natural resource management often fail to produce desired results such as responsible representation, democracy and local development. This study therefore seeks to examine why the implementation of decision making in decentralized forest resource management has failed to achieve desired results of sustainable forest resource management and local development in the Dimako Council and Kongo Community Forests. It further examines the possible implications of the failure of this policy on the development of the local community and country as whole. The decision theory constitute the framework of analysis in this study and the study is mainly qualitative, based on desk review which consists of survey of existing relevant literature, interviews, selected case studies of Dimako and Kongo Council and Community Forest respectively and document analysis Findings suggest that, the decentralization of forest management in Cameroon is finally an interrupted process, obstructed halfway by regional level forces who are considered as mid-level actors and by local community chiefs. Most of those who make up members of council and community forest management committees are nominated, co-opted and not voted. The same persons keep rotating and acting as councilors and at the same time as members of the local development committee as well as members of the forest resource management committees. More so, these committees work together with the Major and seal deals with the elites and do not feel accountable to the local population. The Mayor serves as the sole decision maker in matters that have to do with council forest management and its proceeds. Therefore, many factors account for the failure of this new reform to achieve desired results and these include; Limited transfer of decision making functions to the committees and tendencies of centralization, mismanagement of decision making functions, decision making traps among others. Cameroon government should therefore democratize local government first, implement capacity building before devolution of power, develop and enforce an ethical code, institute and implement ethics as part of the management committee training and orientation programs, incorporate ethics as part of performance evaluation and create an ethical environment to ensure that the actions of senior officials are consistent with expectations.
Keywords: decentralization; forest resource management; decision making; Cameroon; forestry; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|